Phase Equilibrium of Ternary System Cd2+, K+//Cl–-H2O at 298 K - Huang, Y.; Zeng, Y.; Zou, F. (Asian Journal of Chemistry, 2012)
Solid-liquid equilibrium of ternary system Cd2+, K+//Cl–-H2O at 298 K were studied by an isothermal solution saturation method. Experimental results indicate that there are four univariant curves AE1, E1E2, E2E3 and E3B, three invariant points E1, E2, E3 and four crystallization fields in the ternary system. The ternary system has two double salts Cd3KCl7·4H2O and KCdCl3. The crystallization zones of equilibrium solid phases are CdCl2·H2O, KCl, Cd3KCl7·4H2O and KCdCl3, respectively. The composition of the invariant point E1 is KCl and KCdCl3. The composition of the invariant point E2 is Cd3KCl7·4H2O and KCdCl3. The composition of the invariant point E3 is Cd3KCl7·4H2O and CdCl2·5/2H2O. The physico-chemical properties of solution in the ternary system show regular changes along with the increased cadmium concentration. The results indicated that CdCl2·5/2H2O possessed the highest solubility among those three salts, which means a strong transfer of Cd ion and a high pollution risk of soil environment. The solubility of KCdCl3 would be restrained as the salts existing together.